PERATAAN LABA (INCOME SMOOTHING) DAN ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHINYA (STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA - ARIK PRABAYANTI, NI LUH PUTU; WIRAWAN YASA, GERIANTA (Jurnal Ilmiah Akuntansi dan Bisnis, 2011)
The aim of this research is to identify factors influencing incomesmoothing. Income smoothing is an active manipulation of earnings toward apredetermined target. The target may be set by the management, requested bythe analysts, or expected by a particular group of stakeholders (Chong, 2006).The factors being examined were size of the company, company’s profitabilityratios, company’s financial leverage ratios, company’s institutional ownershipratio and auditor reputation. Index Eckel is used to determine the incomesmoothing practices.The sample of 41 manufacturers listed on Indonesian StockExchange, during a period between 2004-2008.The hypothesis were tested using binary logistic regression. The firsthypothesis was formulated to consisted examine the effect of size of thecompany on income smoothing. The second hypothesis was formulated toexamine the effect of company’s profitability ratios on income smoothing Thethird hypothesis was to examine the effect of company’s financial leverage onincome smoothing. The fourth hypothesis was formulated to examine the effect ofcompany’s institutional ownership ratio on income smoothing. The fifthhypothesis was to examine the effect of auditor reputation on income smoothing.The result of this research showed that some of the listed manufacturerson Indonesian Stock Exchange committed income smoothing practices. Binarylogistic regression showed that just company’s profitability ratios affect incomesmoothing,while size of the company, company’s financial leverage ratios,company’s institutional ownership ratio and auditor reputation did not affect theincome smoothing.
Keywords: size of the company, company’s profitability ratios, company’s financial leverage ratios, company’s institutional ownership, ratio auditor reputation and income smoothing